2018
DOI: 10.1080/13651501.2018.1480786
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a culturally adapted behavioural family psychoeducational programme in patients with schizophrenia in Egypt

Abstract: These results demonstrate the feasibility and effectiveness of implementing family therapy psychoeducational interventions in different cultural settings, with relatively minor modifications. This may have implications for mental health policy makers to make available such programmes for patients and mental health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
3
12
0
1
Order By: Relevance
“…Compared to the control group, a significant reduction in patients’ psychiatric symptoms was found at immediate, one‐month, and three‐month follow‐up interventions, which was consistent with most previous research on family psychoeducational programs in schizophrenia (Khalil et al, 2018; Sharif et al, 2012). Besides providing information about the nature, prognosis, and treatments of schizophrenia (e.g., medication regimen), a brief FAM‐SOTC intervention help patients and family caregivers explicate their concerns (e.g., benefits of antipsychotics or barriers to treatment), formulate therapeutic goals, and draw on their awareness of strengths and potential resources (e.g., supportive networks) to support each other in managing patients’ mental illness issues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared to the control group, a significant reduction in patients’ psychiatric symptoms was found at immediate, one‐month, and three‐month follow‐up interventions, which was consistent with most previous research on family psychoeducational programs in schizophrenia (Khalil et al, 2018; Sharif et al, 2012). Besides providing information about the nature, prognosis, and treatments of schizophrenia (e.g., medication regimen), a brief FAM‐SOTC intervention help patients and family caregivers explicate their concerns (e.g., benefits of antipsychotics or barriers to treatment), formulate therapeutic goals, and draw on their awareness of strengths and potential resources (e.g., supportive networks) to support each other in managing patients’ mental illness issues.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to the control group, a significant reduction in patients' psychiatric symptoms was found at immediate, one-month, and three-month follow-up interventions, which was consistent with most previous research on family psychoeducational programs in schizophrenia (Khalil et al, 2018;Sharif et al, 2012). A reduction of caregiver burden and its domains (i.e., caregivers' perceived feeling of over sacrifice, patients' over dependence on the caregiver, negative caregiving feelings, and perceived uncertainty about patient's future) was found at immediate and one-month follow-up post-intervention; however, a brief FAM-SOTC intervention failed to diminish caregiver burden at the three-month follow-up.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, three from reviewed studies (Barrio & Yamada, 2010; Ngoc et al, 2016; Rami et al, 2018) reported a significant improvement in their quality of life for the intervention group. This type of PEIs helps PDwS to focus on the factors that can help them develop strategies to improve their quality of life (Khalil et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…45 The questionnaire was subsequently validated in Korean 46 and in Turkish; 47 its reduced 10-item version was used in an Egyptian study. 48 In Tunisia, it was validated by the study of Nakhli et al, 49 which examined a sample of 204 outpatients with schizophrenia, reporting 7 factors responsible for 59.9% of the overall variance, with a Cronbach's alpha of 0.88. The DAI-30 was used in numerous studies as a questionnaire for predicting adherence in schizophrenia and major depression patients.…”
Section: Drug Attitude Inventorymentioning
confidence: 99%